Strategy for managing patients with severe cases of rosacea - I. G. Sergeyeva; Yu. M. Krinitsyna (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents 3 clinical observations of women of 51, 55 and 57 years old with severe rosacea, who reached the state of remission after a prolonged course of systemic therapy with low doses of isotretinoin. Cumulative dose of isotretinoin for persistent clinical remission was 46.4 mg/kg of weight, 17.6 mg/kg, 12.6 mg/kg respectively. Difficulties related to the subjective perception of patients of his condition has limited the possibility of increasing daily dose of isotretinoin, and the lack of result from the previous therapy with basic medications has made isotretinoin a drug of choice.